Optimalisasi Kinerja Guru Pendidikan Agama Islam dalam Meningkatkan Mutu Pendidikan - Syafri Fadillah Marpaung; Nisa Miranda; Mai Syaroh; Tri Fatimah (Fitrah: Journal of Islamic Education, 2023)
Improving the quality of Islamic religious education is a must, one of which is by optimizing teacher performance. Each educational institution has a different way. For this reason, this study aims to analyze efforts to optimize the performance of Islamic Religious Education teachers in improving the quality of educators at Budi Agung Medan Private High School. The method used is qualitative with a descriptive study approach. Research informants of Islamic religious education teachers and school principals. Collecting data using observation, interviews and documentation studies. Data analysis uses cycles of data collection, data reduction, data presentation, and drawing conclusions. Data validity guarantee techniques use triangulation and member crosscheck. The results showed that optimization was carried out by assigning teachers according to areas of expertise, creating working groups, supervising teachers in administration and training for improvement, giving teacher achievement rewards, building family ties at school. The problems in optimization are the lack of institutional cooperation with partners, the lack of additional training or education, there is a wrong mindset about the limitations of teacher tasks.